(untitled) (Journal of Economic Research & Business Administration, 2018)
Competitiveness means the ability to compete and is one of the main features of a market economy. The ability to compete is the main condition for self-realization in various spheres of the socio-economic system of the country’s economy through the development and creation of new competitive goods and services. The competitiveness of the country’s economy is one of the main indicators reflecting the state of the economy and the prospects for its development. And for our country, the President in his Message poses the task of creating a new model of economic growth that will ensure the country’s global competitiveness. The purpose of this article is to analyze various methods for assessing the level of competitiveness of the economy and choosing the most appropriate methodology for Kazakhstan. The study examined the definitions of competitiveness from different points of view, studied the methods for assessing the World Economic Forum and the Institute for Management Development, identified the advantages and disadvantages of each of them, and carried out a comparative analysis of the methodologies for their main characteristics. As a result of the study, the evaluation methodology proposed by the World Economic Forum was chosen to assess the economy of Kazakhstan and to determine further development prospects.